2008
DOI: 10.1111/j.1745-4530.2007.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rotation on Process Time of Thermally Processed Mackerel in Oil in Aluminum Cans

Abstract: This study was conducted to standardize the optimum processing condition for thermal processing of mackerel in refined groundnut oil in aluminum cans. The standardization of the product was carried out in still retort at 121.1C at three different Fo (accumulated lethality) values, i.e., 5, 7 and 9. The total process times required to reach the Fovalues 5, 7 and 9 were 34.06, 41.29 and 45.09 min, respectively. The Fo9 was selected for further rotation studies based on sensory analysis and sterility test. Rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…There was, however, a difference (P<0.05) for average time to maximum temperature for 6 RPM versus 11 RPM, with the higher rotational speed resulting in a shorter average time ( Figure 5). This effect was observed in other published research where an increase in speed of rotation led to an overall reduction in total process time for a product that had broken heating characteristics (Bindu and Srinivasa Gopal, 2008;Ansar Ali et al, 2008). Additionally, Rattan and Ramaswamy (2014) also found a significant relationship between lethality level, rotational speed, color, and texture differences.…”
Section: Retort Rack Locationsupporting
confidence: 78%
“…There was, however, a difference (P<0.05) for average time to maximum temperature for 6 RPM versus 11 RPM, with the higher rotational speed resulting in a shorter average time ( Figure 5). This effect was observed in other published research where an increase in speed of rotation led to an overall reduction in total process time for a product that had broken heating characteristics (Bindu and Srinivasa Gopal, 2008;Ansar Ali et al, 2008). Additionally, Rattan and Ramaswamy (2014) also found a significant relationship between lethality level, rotational speed, color, and texture differences.…”
Section: Retort Rack Locationsupporting
confidence: 78%
“…These results agree with previous research about oscillating motion increasing the average heating slope and decreasing processing time compared to static mode (Trevino ). Several comprehensive studies have shown that reciprocating agitation can reduce process times and increase the rate of heat penetration when used during in‐container processing (ALI and others ; Singh and others , ). Specifically, within the 9 different treatment combinations there was a significant difference between both motions in LV‐MRA, LV‐HRA, and MV‐HRA ( P < 0.05; Table ).…”
Section: Resultsmentioning
confidence: 99%